Psychological well-being of a pedagogue in the conditions of war - Bolotnikova, Inga; Kucherhan, Yelyzaveta; Vyshnyk, Olha; Shyrobokov, Yurii; Dzykovych, Olha (Revista Eduweb, 2023)
The research is aimed at analyzing the process of forming an educator's psychological well-being in wartime, its consequences, and the peculiarities of interaction. During the study, scientific methods were utilized to examine psychological well-being and its role as a crucial component in creating a positive psychological atmosphere within educational teams. The article highlights the significance of scientific approaches towards shaping the concept of psychological well-being. It explores the use of a pedagogue's personal psychological well-being in wartime as a means of stabilizing the social sphere and disseminating the quality of such a policy to achieve a strategic victory while countering the information and psychological attacks of the aggressor country. The study's outcomes have the potential to enhance the ability to respond to external stimuli, leveraging emotional resources to mitigate stress and enhance the quality of the educational process.